TINJAUAN YURIDIS TERHADAP TANDA BUKTI HAK SEBAGAI PETUNJUK KEPEMILIKAN HAK ATAS TANAH (STUDI PUTUSAN PENGADILAN NOMOR 41/PDT.BTH/2019/PN KUPANG) - Wungo, Anna Xaveria Ekaputri; Mauritius, Darius; Bire, Chatryen M Dju (Petitum Law Journal, 2025)
Land disputes in Indonesia often give rise to complex legal problems, especially those related to certainty of ownership of land rights. This research aims to analyze the strength of evidence in the land dispute between CF as the plaintiff and LT as the defendant, based on Court Decision Number 41/PDT.BTH/2019/PN Kupang. This case involves land located in Oepura Village, Kupang City, which is claimed as inheritance by both parties. The research method used is normative juridical research with a case approach. Data was obtained through literature study and analysis of documents submitted in the trial. The evidence examined includes Certificates of Ownership Rights, Land Reform Letters, as well as various previous court decisions. The research results showed that the evidence submitted by the plaintiff, even though it included formal documents such as Certificates of Ownership and Supreme Court Decisions, was considered not clear enough in describing the boundaries of the disputed land. On the other hand, the evidence presented by the defendant, including previous court decisions and executorial letters, is considered stronger because it shows continuity of ownership and legal validity. The conclusion of this research is that in land disputes, the court not only considers formal documents such as land certificates, but also the clarity of the land object in dispute. The strength and consistency of evidence is the main factor in determining the direction of the court's decision. In this case, the court sided with the defendant because the evidence presented was stronger and supported the land ownership claim.